파독 광부의 이동 자본(mobility capital): 광산 노동자 이후 직업이동 궤적 - 최영미; Young-mi Choi (다문화와 평화, 2025)
본 연구의 주요한 목적은 파독 광부들이 광부 계약 만료 후 독일 사회에서 직업이동 과정과 사회경제적 지위 획득 전략이 어떠하였는지를 분석하는 것이다. 분석을 위하여 1960년대 독일에서 탄광 노동자로 시작하여 다양한 직업으로 전환한 경험이 있는 광부들을 독일 현지에서 심층 인터뷰한 자료를 사용하였다. 분석 결과, 파독 광부들은 독일 사회로의 정착을 위한 열망으로 직업이 하향이동하고, 이동의 제약이 따르는 광부를 선택했음에도 불구하고, 계약 종료 후 새로운 삶을 시작하며 사회적 지위와 정체성의 변화를 겪었다. 이들은 대부분 비숙련-숙련 노동자의 지위를 유지하거나 자영업에 의존하게 되었고, 사회적 이동성은 제한적이었다. 본 연구는 그동안 파독 광부의 독일 내 사회 이동 과정과 전략을 밝혀냈다는 점에서 의의를 가진다. The primary objective of this study is to analyze the process of occupational mobility and the strategies for acquiring socioeconomic status among Korean miners in German society after the expiration of their mining contracts. For the analysis, data from in-depth interviews conducted with miners in Germany who started as coal miners in the 1960s and transitioned to various occupations were used. The analysis revealed that despite experiencing downward occupational mobility and choosing the mining profession with its inherent mobility constraints due to their aspiration to settle in German society, these Korean miners underwent changes in social status and identity as they began new lives after their contracts ended. Most of them maintained the status of unskilled-to-skilled laborers or became dependent on self-employment, and their social mobility was limited. This study is significant in that it sheds light on the process and strategies of social mobility among Korean miners within Germany.